PENGRAH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SKINDCARE DENGAN PRICE DISCOUNT SEBAGAI VARIABEL MODERASI : (STUDI PADA PEGAWAI BANK NTT PUSAT CABANG KUPANG) - Stella Sahetapy; Maria C.B Manteiro (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the influence of brand image on skincare purchase decisions among employees of Bank NTT Kupang and how price discounts moderate the relationship between brand image and skincare purchase decisions among employees of Bank NTT Central Kota Kupang. Method: The study uses a quantitative method with multiple linear regression analysis techniques and Moderated Regression Analysis (MRA) with the assistance of SPSS. The research sample consists of 30 respondents from Bank NTT Kupang Branch employees with the following criteria: 1) women aged 25-50 years, 2) using skincare for daily facial care (active skincare product users), 3) having basic knowledge about skincare.Results: The research results show that brand image has a positive and significant effect on purchase decisions, meaning that the better the brand image of skincare products, the more likely consumers are to buy the product. Meanwhile, price discount moderates the relationship between brand image and purchase decisions positively and significantly, meaning that the higher the price discount of a product, the greater or stronger the positive influence of brand image on purchase decisions. In other words, price discount can increase the impact of brand image on purchase decisions. The suggestions given include improving the product's brand image, maximizing price discount programs, and strengthening the market segment. Keywords: Brand image, decision making, price discountConclusion of these findings shows that the better the brand image of a product, the higher the tendency of consumers to make a purchase. In addition, price discounts have been proven to be able to positively and significantly moderate the relationship between brand image and purchase decisions, so the presence of price discounts can strengthen the influence of brand image on purchase decisions. Keywords: Brand Image, Decision Making, Price Discount